ANALISIS REGRESI LOGISTIK BINER PADA FAKTOR RESIKO KEJADIAN TUBERKULOSIS - Findasari; Ade Ima Afifa Himayati (Jurnal Matematika Sains dan Teknologi, 2023)
Tuberculosis is the disease with the second highest mortality rate in the world and is ranked first in the most deadly infectious disease. In Indonesia, tuberculosis occurred around 969,000 cases that were found, which is up about 17% from the previous year, which means that there are 354 people out of 100,000 people who have tuberculosis. This study aims to determine the risk factors that can influence the incidence of pulmonary tuberculosis (TB) and find out the risk factors that have a relationship with the incidence of pulmonary tuberculosis. Data analysis in this study was carried out by the binary logistic regression method. The results of the study stated that factors of nutritional status and family history status suffering from tuberculosis had an influence on the incidence of tuberculosis. In addition, risk factors that are related to the incidence of pulmonary tuberculosis are nutritional status, family history status of tuberculosis, and smoking habits, while economic status or income has no influence or association with the incidence of pulmonary tuberculosis.